GERAK DAN ROTASI BUMI: REALITAS ILMIAH DALAM AL-QURAN: Menelusuri Bukti Ilmiah dalam Kitab Suci A-Quran - Nur Hayati; Indah Riskilawati; Muhammad Idzhar Alfajri; Ahmad Paisal; Arya Rosyid Ridho (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Abstract This article examines the phenomenon of the earth's motion and rotation, as well as how this scientific reality is explained in the Quran. The rotation of the earth on its axis causes the alternation of day and night, as well as the apparent movement of celestial bodies such as the sun, moon, and stars. In addition, the earth's revolutionary motion around the sun affects the change of seasons and the duration of day and night. These phenomena also affect the tides of sea water and the dynamics of the climate on earth. The study links scientific explanations of the earth's motion and rotation with verses in the Qur'an that refer to the phenomenon, demonstrating the harmony between modern science and Islamic teachings. These findings reinforce the belief that the Qur'an contains knowledge relevant to modern science